Register Ng Pagmimina Sa Chavacano: Isang Analisis - Delos Reyes, Roselyn (JPAIR Multidisciplinary Research, 2017)
The language is a communication need to fully accomplish the work. Also, language is used to bargain and speed up the work. One of the variations of the language is the so-called register. The register according to Alcaraz et al. (2005), is also called as style of speech. A person may use different styles in his speech or even in writing to express his feelings. The register is a language variation based on its communication. One of the language registers is the language used by mining miners in Sitio Mina, Barangay Curuan, Zamboanga City. This study is a qualitative research by "Morpho Analysis". The purpose of this study is to examine the lexicon and the meaning of the words in Chavacano used in mining. Similarly, the names, words and phrases used in words. It will also examine the aspect of the Verb language of Chavacano. Based on the research done, mining has been using lexicons or words that are appropriate for their occupation. These words refer to the use, the place, the person, describing and demonstrating the action.
Keywords: Mining; Register; Chavacano